بلاغة الأمثال في كتاب مأساة الحبّ - Abdulkabeer Muhammad jamiu (Nady Al-Adab : Jurnal Bahasa Arab, 2023)
تتضمن الأمثال حكماً بليغة مرتبطة بأساليب البلاغة التي أصبحت لها مكانة مرتفعة في إبداع النّصوص الرّوائيّة. يهدف هذا البحث إلى دراسة الأمثال الواردة في كتاب "مأساة الحبّ" لإبراز دقّة ألفاظه وجزالة تراكيبه وروانق دلالاته وبدائع معانيه لأنّ بلاغة الأمثال أسلوب يتّضح من خلاله الحقائق الصّحيحة الّتي تطابق مواطن الكتاب لمقتضى الحال إذ أصبحت الأمثال مادّةً لنسج هذا الكتاب بالتّعبير المميّز والتّواصل الّلغويّ القيّم لزيادة التّوضيح والتّقرير والتّحقيق الّتي أظهرتها عملية الأمثال في إثراء النّصّ الّلاحق وإنتاجه الجديد. يتجلّى هذا البحث بأنّ الأمثال تمنح هذا الكتاب كلامًا بليغًا فيه محاسن الأساليب البلاغيّة إذ تلمح في أسلوب النّصوص الرّوائيّة بتوضيح الدّلالات وتوسيع السّبك وحسن التّراكيب وسلاسة التّرتيب وفصاحة الألفاظ الّتي تلائم مواطنها السّردية. وينتج هذا البحث أنّ بلاغة الأمثال اكتسبت هذا الكتاب حسن الانسجام، وجمال النّسج وتنسيق العبارات ودقّة التّصوير وتنميق النّصّ ذي القيم البلاغيّة وقوّة التّأثير كما يوصي المؤلّفين بتدقيق معرفة استعمال الأمثال والباحثين بميل دراساتهم إلى المجالات الّلغوية الأخرى في الكتب الرّوائيّة المؤلّفة.      الكلمات المفتاحيّة: البلاغة؛ الأمثال؛ الدّلالة؛ الّلغة؛ النّصّ. ABSTRACT The proverbs involve eloquent aphorisms linked linguistically with rhetorical styles in an exalted status while creating fictional texts. This article aims to study the mentioned proverbs in the book titled ‘Ma’asatul-hubb’ in order to discover an accuracy in its eloquent words, a profusion in its symmetrical structures, a glamour in its coordinated conceptions and an unique in its semantic textures. The study signifies that the proverbial eloquence is a linguistic style that exposes essential denotations of proverbs which are compatible with their textual spots in the book. The proverbs have rhetorical peculiarities being among the components of forming the book, an agent of expressional perception, a medium of standard linguistic connectivity for clarifying, affirming and accomplishing the fictional text. The study discovered that the proverbs confer upon the book eloquent speeches, linguistic proportions, stylish expressions, magnificent connotations and exceptional significances. The study concluded that the incorporated proverbs in this book display the qualities of rhetorical styles that insinuate the unique textual composition in elucidating its systemization and words which proverbial eloquence enriches the book appropriately with qualitative euphuisms, adequate symphonies, coordinated phrases, accurate formations, perfected euphemisms, harmonious compositions, artistic influences and standard rhetorical texts. KEYNOTES: Fiction; linguistic; proverbs; rhetoric; semantic